Answer:
C. x = 3, y = 2
Step-by-step explanation:
If both triangles are congruent by the HL Theorem, then their hypotenuse and a corresponding leg would be equal to each other.
Thus:
x + 3 = 3y (eqn. 1) => equal hypotenuse
Also,
x = y + 1 (eqn. 2) => equal legs
✔️Substitute x = y + 1 into eqn. 1 to find y.
x + 3 = 3y (eqn. 1)
(y + 1) + 3 = 3y
y + 1 + 3 = 3y
y + 4 = 3y
y + 4 - y = 3y - y
4 = 2y
Divide both sides by 2
4/2 = 2y/2
2 = y
y = 2
✔️ Substitute y = 2 into eqn. 2 to find x.
x = y + 1 (eqn. 2)
x = 2 + 1
x = 3
Answer:
tha
Step-by-step explanation:
Answer:
is the number 4
so 13/16 3/16
Step-by-step explanation:
Y=x^2-5, solve for x
y+5=x^2
x=√(y+5) so
f^-1(x)=√(y+5)